Models to Estimate Longitudinal Compressive Strength of Brazilian Hardwood Based on Apparent Density - Rocco Lahr, Francisco Antonio; Arroyo, Felipe Nascimento; Castanheira Rodrigues, Edson Fernando; Boff Almeida, Joao Paulo; Moura Aquino, Vinicius Borges de; Vobornik Wolenski, Anderson Renato; Santos, Herisson Ferreira dos; Nonato Ferraz, Andre Luiz; Chahud, Eduardo; Molina, Julio Cesar [UNESP]; Pinheiro, Roberto Vasconcelos; Christoforo, Andre Luis (North Carolina State Univ Dept Wood & Paper Sci, 2021)
As wood is an orthotropic and natural material, there are several properties required for its use in civil construction. The apparent density has been used to estimate physical and mechanical properties of wood, as it is easy to determine experimentally, unlike other determinations, which involve the use of equipment available only in large research centers. Using the Brazilian standard ABNT NBR 7190 and linear and non-linear regression models, this research aimed to evaluate their accuracy in estimating the compressive strength parallel to the fibers (f(c0)) as well as their characteristic value (f(c0,k)). This study considered 72 tropical wood species from native forests that were divided into the 4 strength classes of this standard. For the set formed by all species, the linear polynomial model was the best fit, resulting in a determination coefficient of just over 70%.
Keywords: Hardwoods; Longitudinal compressive strength; Apparent density; Regression models